Polycationic nanoparticle-integrated inherently antibacterial cryogels - Daaboul, Maria; Akgul, Busra; Tasdurmazli, Semra; Abamor, Emrah Sefik; Ozbek, Tulin; Ozmen, Mehmet Murat; Topuzogullari, Murat (ELSEVIER, 2024)
Inherently antibacterial polycations have been of interest in the pursuit of overcoming antibiotic resistance. In this study, we have prepared a new cryogel system incorporating polycationic nanoparticles composed of 4-vinylpyridine (4VP) and oligo(ethylene glycol) methyl ether methacrylate (OEGMA), which possess inherent antibacterial properties. The incorporated polycationic nanoparticles were successfully attached to the pore wall surfaces of the cryogels with quaternization reaction. While the cryogel's pore size was 50 +/- 10 mu m, the diameter of the nanoparticles attached on the pore surfaces was 150 +/- 16 nm. The prepared nanoparticle-integrated cryogels revealed a high biocompatibility on L929 mouse fibroblast cells and antibacterial activity against both E. coli and S. aureus bacteria. These cryogels have potential in numerous applications including antibacterial surfaces, wound dressings and tissue engineering.
Keywords: Antibacterial; Biomaterials; Cryogel; Nanoparticles; Polycation; Quaternization; Materials Science; Physics